Fault tree analysis of fires on rooftops with photovoltaic systems - Mohd Nizam Ong, Nur Aliah Fatin; Sadiq, Muhammad Adnan; Md Said, Mohamad Syazarudin; Jomaas, Grunde; Mohd Tohir, Mohd Zahirasri; Kristensen, Jens Steemann (Elsevier, 2022)
A fault tree analysis of fires related to photovoltaic (PV) systems was made with a focus of understanding the failure rate of the electric components. The failure rate of different components of these systems was calculated from data obtained from reports, research studies, and fire incident statistics of four countries. The results explain the significant causes of fire on the component level and various failure patterns resulting in PV-related fires. The qualitative analysis identified seven major events that led to incidents caused by a PV-related ignition source, with electrical arcing being the main cause of fires. This finding is highly related to the imprudent installation practices due to negligence and low awareness of the fire risk associated with PV systems by installers. The quantitative results show that 33% of the PV fire incidents are due to unknown or unrelated ignition sources, indicating that great focus should be given to mitigate the consequences caused by PV-related fires. The PV module, isolator, inverter, and connector are the major PV system components that are highly responsible for the ignition of PV-related fires, with the connector being the prime contributor in 17% of the PV-related fires. Finally, the quantitative analysis established an annual fire incident frequency of 0.0289 fires per MW. The results enable estimation of the number of fire incidents linked to the installed PV capacity, and the fault tree analyses highlight where improvements are most critical. Based on the results of the analyses, two questions are suggested for implementation in the post-incident reports of the national fire and rescue services.